THE DYNAMICS OF ENGLISH LANGUAGE CHANGE FROM THE OLD ERA TO THE DIGITAL AGE - Murtiani, Rahmila (Indonesian Journal of Applied Linguistics, 2012)
Abstract: This article attempts to discuss why and how English has changed, tracing from particular features such as spelling, vocabulary, grammar, and meaning from Old English era until Modern English, how the peopleâ€™s attitude toward the changes, and whether these changes ruin or contribute to the development of English as a global language.Â  As a final remark, this article will also offer a few suggestions on how the phenomenon of language change should be treated particularly on the relation with English language teaching and learning. Key words: language change, form, meaning, attitude